The use of indexs objective grading system and smile line for evaluating the balance functional occlusion in orthodontic treatment - Damaryanti, Endah; Thahar, Bergman; Salim, Jono; Mardiati, Endah (Universitas Padjadjaran, 2014)
Introduction: Orthodontic treatment has a main purpose to reach balanced functional occlusion and create a harmonic esthetic face. But several studies indicates that orthodontic treatment influence smile esthetics, especially smile arc and buccal corridor. One-third of the treated patients showed a flat smile arc and orthodontic treatment with extraction resulted in excessive buccal corridors. The purpose of this research is to evaluate the difference of the Objective Grading System index, developed by the American Board of Orthodontics (ABO) and smile aesthetics in patients with Class I dentoskeletal malocclusion before and after orthodontic treatment. Methods: Twenty dental casts, panoramic radiographs and grouped pre and post-treatment. Dental casts and panoramic radiographs are scored according to the guidelines of the Objective Grading System. Extra-oral photographs were assessed by researcher using modified Goldstein dentofacial analysis. Result of measurements were evaluated with statistical t-test. Results: Results of the research indicates Objective Grading System index and also score of smile esthetics before and after orthodontic treatment shows difference statistically (for Objective Grading System index P = -1121 > 2.09 and for smile esthetics P = 5.15 > 2.09). Conclusions: Extremely weak relationship was found between Objective Grading System index and Aesthetics smiles.